The optimal regional irradiation volume for breast cancer patients: A comprehensive systematic review and network meta-analysis of published studies - Qi, Wei-Xiang; Cao, Lu; Xu, Cheng; Cai, Gang; Chen, Jiayi (Frontiers in Oncology, 2023)
Background Currently, the optimal adjuvant regional nodal irradiation (RNI) volume for breast cancer (BC) remained controversial. We aimed to define the optimal RNI treatment volume for BC by using a comprehensive network meta-analysis (NMA) of published studies. Materials and methods PubMed, Embase, Medline, and Cochrane Central Register of Controlled Trials were searched from database inception to 30 May 2022. Studies assessing different adjuvant RNI volumes for BC were eligible for inclusion. The primary outcome was overall survival (OS), and secondary outcome was disease-free survival (DFS) and distant-metastasis-free survival (DMFS). Results A total of 29,640 BC patients from twenty studies were included. The pooled hazard ratio demonstrated that internal mammary node irradiation (IMNI) in BC patients significantly improved OS giving HR (hazard ratio) of 0.87 (95%CI: 0.83–0.91, p<0.001), DFS with HR of 0.78 (95%CI: 0.68–0.90, p<0.01), and DMFS with HR of 0.87 (95%CI: 0.79–0.97, p<0.01) when compared to controls. Sub-group analysis indicated that RNI with IMNI significantly improved OS (HR 0.87, 95%CI: 0.81–0.93, p<0.01), DFS (HR 0.65, 95%CI: 0.56–0.77, p<0.01), and DMFS (HR 0.90, 95%CI: 0.82–0.98, p=0.02) when compared to RNI without IMNI. NMA showed that CW/WB (chest wall/whole breast) + RNI with IMNI significantly improved DFS (HR 0.93, 95%CI: 0.86–1.00) and DMFS (HR 0.90, 95%CI: 0.81–0.99), but not for OS (HR 0.93, 95%CI: 0.84–1.03) when compared to CW/WB alone. Based on the analysis of the treatment ranking, CW/WB+RNI with IMNI appeared as the best treatment approach for BC patients. Conclusions Our pooled results demonstrated that RNI with IMNI yielded a significant survival advantage for BC patients. NMA showed that CW/WB+RNI with IMNI was the optimal radiation volume for BC patients.